AICCRA Online Internal feedback module - Ramírez, Margarita M.; Tobon, Hector (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The AICCRA Knowledge and Data Sharing team are continuously adapting the Managing Agricultural Research for Learning and Outcomes (MARLO) system for capturing progress towards our Key performance indicators, activities, and deliverables. The system is fully operational and is supporting the project to capture our planning, progress, and final reports. During this progress report, we introduced a new module that allows the Project Management Committee to provide feedback to Cluster Leaders considering that for us it is essential to capture consistent and high-quality information in MARLO.